ANALISIS KEMAMPUAN LITERASI SAINS SISWA PADA PEMBELAJARN IPAS KELAS IV SD NEGERI 1 SYAMTALIRA BAYU - Reni Kartika; Zainal Abidin; Rahmiaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to identify the abilities and challenges related to students’ science literacy in IPAS (Integrated Natural and Social Sciences) learning. This is a qualitative research study using a descriptive method. The research sample consisted of 5 students selected from 25 fourth-grade students in class IV B. The data collection methods used in this study were interviews and observations. This study aims to describe: 1). The science literacy abilities of fourth-grade students at SD Negeri 1 Syamtalira Bayu in IPAS learning. 2). The challenges students face in relation to science literacy in the context of IPAS learning. The results of the study show that: 1). The science literacy abilities and knowledge of fourth-grade students at SD Negeri 1 Syamtalira Bayu are generally in the moderate category, both in terms of content and process aspects. Students show basic abilities in recognizing, connecting, and applying scientific concepts, which still need to be improved through contextual and reflective learning approaches. 2). The challenges faced by the students in IPAS learning include a lack of interest in the subject matter and low learning readiness, which negatively impact their understanding of concepts and scientific thinking skills.